The effect of essential skills on perceived employability: a case of Malaysian undergraduates in energy-focused universities - Mohamad N.M.; Jaaffar A.H.; Abd Majid N.; Isa A. (Emerald Publishing, 2025)
Purpose: The purpose of this study is to examine the effect of technical skills, soft skills and social mobility skills on the perceived employability of Malaysian undergraduates in energy-focused universities. This study also aims to investigate the moderating effects of academic performance on such relationships. Design/methodology/approach: To accomplish these objectives, this study employed partial least squares-structural equation modelling (PLS-SEM) to analyse data obtained from 247 Malaysian undergraduates from public and private energy-focused universities across Malaysia. The Human Capital Theory served as the overarching theoretical framework for the study. Findings: The study reveals that even if an undergraduate has stellar grades, they will not help him/her to land a job if they lack basic technical and computing skills. This study also indicates that undergraduates? current academic performance affects their perceived employability despite already possessing the necessary soft skills. Along with academic performance, social mobility skills can be a determining factor in how graduates see their own employability. This is because social mobility has a significant impact on graduates? chances of finding gainful employment. Research limitations/implications: This study provides insights into how technical skills, soft skills and social mobility skills influence the perceived employability of Malaysian undergraduates, especially in energy-focused universities, and the role of various parties involved. These parties, such as higher education institutions, are the key players that can initiate strategies to enhance specific skills and steer a public conversation towards a more methodical strategy for boosting graduates? employability for future employment. This research also sheds light on how to better prepare for emerging job opportunities in the energy sector. Originality/value: The study examines the effect of technical skills, soft skills and social mobility skills on the perceived employability of Malaysian undergraduates in energy-focused universities for future employment among Malaysia?s universities? graduates. By providing a multidisciplinary viewpoint, this study paves the way for future research partnerships among experts in higher education, researchers in related fields and career researchers. ? 2024, Emerald Publishing Limited.